2020
DOI: 10.2478/amph-2022-0035
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and Students’ Motivation: Using Quizizz in the English as a Foreign Language (EFL) Classroom

Abstract: During the last years, gamification has been regarded as a powerful tool to transform the EFL classroom into an engaging and entertaining learning context. The present paper aims to give insight into how gamification affects students’ intrinsic and extrinsic motivation. With a sample of 51 students of a state school located in Almazora (Castellón, Spain), an experimental group and a control group were created in order to compare digital to traditional methodologies, respectively. With the implementation of a M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
3
1
2
Order By: Relevance
“…Since it is an appealing learning medium where students can learn and play simultaneously. However, there are differences between a study by Jiménez-Sánchez & Gargallo-Camarillas (2020) and Ekinci (2020) with this present study. The first difference is the gamification used as the learning media.…”
Section: Introductioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Since it is an appealing learning medium where students can learn and play simultaneously. However, there are differences between a study by Jiménez-Sánchez & Gargallo-Camarillas (2020) and Ekinci (2020) with this present study. The first difference is the gamification used as the learning media.…”
Section: Introductioncontrasting
confidence: 93%
“…An experimental research about gamification and students' motivation in English Language Learning was done in 2020. This research showed that 51 Spanish students' intrinsic and extrinsic motivations advance due to gamification in the EFL learning process compared to students who do not use gamification (Jiménez-Sánchez & Gargallo-Camarillas, 2020). Another study in Turkey found that 85% of the 73 participants feel highly motivated due to the implementation of gamification in their learning process.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Gamification has been widely used in several non-English-speaking countries (Zhang & Hasim, 2023) and is considered a robust tool for transforming the EFL classroom into an engaging and entertaining learning environment (Jiménez-Sánchez & Gargallo-Camarillas, 2020). EFL teachers have recognized gamification as an effective method for promoting student engagement, positive learning behavior, and creating an attractive learning environment (Flores-Aguilar, Prat-Grau, Fernández-Gavira, & Muñoz-Llerena, 2023;Mila & Mahbub, 2022).…”
Section: Gamification In the Efl Contextmentioning
confidence: 99%
“…La ludificación en la enseñanza ha demostrado en ocasiones anteriores ser útil en cursos de inglés como lengua extranjera enfocadas en estudiantes de diversas edades y niveles (Jiménez y Gargallo, 2020;Miranda, 2021;Philpott, 2020;Rivera y Sánchez, 2020;Turan y Çimen, 2018). Asimismo, diversos autores han tenido resultados positivos en universidades específicamente.…”
Section: Antecedentesunclassified